The relationship between milk components, immunoglobulins, and cytokine content at the end of lactation in Kyrgyz mares - Istanbullugil, F. R.; Risvanli, A.; Salikov, R.; Bayraktar, M.; Acaroz, U.; Acaroz, D. A.; Uz, M. (South African Journal of Animal Sciences, 2023)
The aim of the present study was to determine the relationship of immunoglobulins and cytokine levels in the milk of Kyrgyz mares during the last period of lactation. For this purpose, seven Kyrgyz mares were used. During the last week of lactation, milk samples were obtained from mares four times at intervals of two days. Physicochemical tests were performed on all collected milk samples, and pH, fat, ash, titratable acidity, and dry matter were measured. Interferon-gamma (IFN-gamma), interleukin - 2 (IL-2), tumour necrosis factor-alpha (TNF-alpha), and immunoglobulin G (IgG) levels were determined using commercial enzyme- linked immunosorbent assay (ELISA) kits. Based on the measurements, the lowest IgG level was determined on the last day of lactation (10.23 +/- 13.13 mu g/mL) and the TNF-alpha level was determined to be the highest on the last day lactation (61.10 +/- 75.69 pg/mL). However, no statistical differences between the days in terms of IFN-gamma, IL-2, pH, titratable acidity, dry matter, ash, and fat were found. Varying degrees of positive correlations between the parameters existed and were more pronounced between IgG levels and pH values. As a result, it was concluded that in the last period of lactation in Kyrgyz mares, IgG concentrations decreased and TNF-alpha levels increased in their milk, but substantial changes in milk composition, immunoglobulins, and cytokine levels in milk did not show positive correlations with the physicochemical properties of milk.
Keywords: cytokine; immunoglobulin; Kyrgyz mare; mare's milk